RETURN OF TRAINING INVESTMENT (ROTI) TRAINING IN PTP NUSANTARA IV - Rohana Sinaga; Harmein Nasution; Nazaruddin Matondang (Universitas Teuku Umar, 2015)
PT PTPN IV (PTPN IV) as one of the state-owned enterprises (SOEs) has made the transformation, including in terms of human resource management. This is reflected in a transformation program which has been launched by the Board of Directors PTPN IV, namely: human resources as the most important asset that must be transformed into a level of qualification that is recognized universally, in the aspects of competence, capability and integrity. To increase knowledge (knowledge), skills (skills) and attitude (attitude) to fit the demands of the post, periodically HR should be given education and training means that the education and training of human resources is an investment that can be interpreted by issuing a number of funds. Evaluation of training can be used as a measuring tool to help identify and analyze the training benefit significantly, demonstrating clear returns for the company, as the basis for evaluation of the training system during this time so that it can be improved in order to contribute to the training of the company. Significant changes occur on the competence of the ex-trainee aircraft operator on duty at the boiler palm oil mill PT PTPN IV, after they followed the training. This is evident from the average value of the competence of the former participants of the training changes are relatively high at 4.27 (good category) of the three domains of competence studied, the greatest changes occur is on the domain of skills of participants increased quality of the work with a score of 4, 44 followed by Attitudes that increased motivation with a score of 4.40, respectively. Return on Training Investment (ROTI), obtained BREAD value of 420%.Keywords: Return on Training Investment (ROTI), training, education, evaluation.